Progestins in hormonal replecement therapy - new perspectives - Tomaszewski, Jacek; Baranowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2003)
In the last years there has been an extraordinary development in the synthesis of new progestins. The action of progestins is a function of many factors: its structure, activity, affinity to the progesterone or to the other steroids receptors, the target tissue considered, dose, and metabolic transformation. Several risks are attributed to progestins as a class-effect; however, progestogens used in hormonal replacement therapy have varying pharmacological properties and do not induce the same side effects. Newly synthesized progestins (19-norprogesterone and 18α-spironolactone derivatives) do not bind to the androgen receptor and do not exert an androgenic side effect. Selection molecules having no estrogenic, androgenic or glucocorticoid effects should allow a larger use of the progestins in HRT without any major drawback.